A1.28 Anti-carp antibodies in two large cohorts of patients with rheumatoid arthritis and their relationship to genetic risk factors and smoking. (31st January 2014) - Jiang, Xia; Trouw, Leendert A; van Wesemael, Tineke J; Shi, Jing; Källberg, Henrik; Malmström, Vivi; Israelsson, Lena; Hreggvidsdottir, Hulda; Verduijn, Willem; Klareskog, Lars; Alfredsson, Lars; Huizinga, Tom W J; et al.
Abstract : Background and Objectives: In rheumatoid arthritis (RA), the presence of antibodies to citrullinated proteins (ACPA) is strongly associated with certain genetic risk factors and smoking. The recently identified antibodies against carbamylated proteins (anti-CarP) are present in part of ACPA-positive, but also ACPA-negative RA patients. This raised the question whether the presence of anti-CarP may be associated with specific risk factors, which could provide clues about the pathogenesis of ACPA-negative RA. In this study we have therefore analysed the relationship between anti-CarP antibodies, ACPA, genetic risk factors ( HLA-DRB1 alleles and PTPN22 ) and smoking in RA. Materials and Methods: Presence of antibodies to carbamylated fetal calf serum (CarP-FCS) and fibrinogen (CarP-Fib) was determined by in-house ELISAs in the Leiden Early Arthritis Cohort (EAC) and in the Swedish Epidemiological Investigation of RA (EIRA) cohort. Odds ratios for associations with different HLA-DRB1 alleles, PTPN22 genotypes and smoking were calculated separately for each cohort as well as in a combined meta-analysis, in RA subsets defined by anti-CarP and anti-cyclic citrullinated peptide (CCP) antibody status. Results: In both cohorts, anti-CarP antibodies were mainly detected in the anti-CCP-positive population, but also in the anti-CCP-negative population. No strong associations between anti-CarP antibodies and specific HLA-DRB1 alleles, including shared epitope alleles, could be identified, with the exception of a consistent association between anti-CarP FCS and HLA-DRB1* 03. Further analyses did not reveal any specific associations between anti-CarP antibodies and PTPN22 genotypes or smoking. Conclusions: Anti-CarP antibodies were present in both ACPA-positive and ACPA-negative RA patients in the two separate cohorts. Except for a modest association with HLA-DRB1* 03, there were no strong associations between anti-CarP antibodies and other HLA-DRB1 alleles, PTPN22 or smoking. Although it cannot be excluded that risk factors not investigated here may be importance for anti-CarP-positive disease, the lack of association found here suggests a possible fundamentally different biological mechanism for anti-CarP antibody formation compared with anti-CCP antibody formation.